Estudio de prefactibilidad para la instalación de una planta productora de snacks de manzana deshidratada - Aizcorbe Santillana, Thais (2020)
The aim of this research is to determine the market, technological, economic, financial, and social viability of the project over five years. In this context, a market study is carried out and the target market is selected. Women between 25 and 39 years-old belonging to economic sectors A and B of zones 7 and 8 of Lima become the ideal target market for dried apple snacks, since they are the ones who mostly pursue a healthy lifestyle and who do not have economic limitations to buy products that may contribute to their lifestyle. They will be able to buy these snacks in supermarkets, convenience stores and organic stores. The price set for these establishments will be S/740 per box, which will include 100 bags of snacks of 40g each. The production plant will be installed in Chilca, district of Lima selected for having more competitive advantages and the plant size corresponds to the market-size relationship, equivalent to 13 010 kilograms of product. The technology necessary to carry out the snacks production process exists and works. Also, the installed capacity of the plant is only limited by the activity of verification and selection of raw material. The company in charge of producing these dried snacks will be the closed company “Snacks MT S.A.C”, whose organization chart will be made up of the CEO, 04 managers, executives, quality inspectors, operators and warehousemen. Regarding the economic and financial viability of the study is validated that, in the positive and pessimistic scenario proposed, the NPV is positive, the IRR is greater than the cost of capital (16%) and the B/C ratio is greater than zero, in both cases. Lastly, regarding the social evaluation of the study is shown that the implementation of the plant will bring new job opportunities.